2016
DOI: 10.1080/10286020.2016.1235562
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antioxidant activity of curcumin analogs

Abstract: Numerous biological activities including antioxidant, antitumor, anti-inflammation, and antivirus of the natural product curcumin were reported. However, the clinical application of it was significantly limited by its instability, poor solubility, less body absorbing, and low bioavailability. This review focuses on the structure modification and antioxidant activity evaluation of curcumin. To study the structure-activity relationship (SAR), five series of curcumin analogs were synthesized and their antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
2
28
1
1
Order By: Relevance
“…This result is inconsistent with our previous study on the Mannich base derivatives of dehydrozingerone (DHZ), which indicated that most of the compounds' Mannich bases exhibited higher free radical scavenging activity than DHZ [21]. In curcumin analogs, electron-donating substituents at ortho positions relative to the phenol groups enhance antioxidant activity, while bulky alkyl substituents inhibit it [22,23]. Mannich bases can also enhance or lower cyclovalone's free radical activity: the higher the basicity of the nitrogen atom of the Mannich base derivative of cyclovalone, the higher the DPPH free radical scavenging activity of the compound [14].…”
Section: Anti-inflammatory and Antioxidant Activitycontrasting
confidence: 90%
“…This result is inconsistent with our previous study on the Mannich base derivatives of dehydrozingerone (DHZ), which indicated that most of the compounds' Mannich bases exhibited higher free radical scavenging activity than DHZ [21]. In curcumin analogs, electron-donating substituents at ortho positions relative to the phenol groups enhance antioxidant activity, while bulky alkyl substituents inhibit it [22,23]. Mannich bases can also enhance or lower cyclovalone's free radical activity: the higher the basicity of the nitrogen atom of the Mannich base derivative of cyclovalone, the higher the DPPH free radical scavenging activity of the compound [14].…”
Section: Anti-inflammatory and Antioxidant Activitycontrasting
confidence: 90%
“…The selectivity and sensitivity of DAPs towards cancer cells, and the dosages that vary among the cancer cells remain unclear and are not fully understood. To the best of our knowledge, the majority of DAPs demonstrated poor radical scavenging activity although it is common that the presence of hydroxyl group on phenyl ring is important in scavenging free radicals [ 88 , 89 ]. Previous studies showed that antioxidants may serve as cancer promoting agents [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Coordination of lysine to the enolic hydroxyl group of curcumin seems to slightly reduce the antioxidant properties of the curcumin salt. Indeed, the electron-donating groups such as the phenolic and enolic hydroxyl groups are essential to the antioxidant activity of curcumin [23,24]. Morales et al [25] suggested that curcumin and its derivatives principally act as chain breaking antioxidants rather than as direct free radical scavengers.…”
Section: Discussionmentioning
confidence: 99%